In Vitro Neurochemical Assessment of Methylphenidate and Its “Legal High” Analogs 3,4-CTMP and Ethylphenidate in Rat Nucleus Accumbens and Bed Nucleus of the Stria Terminalis - Davidson, Colin; Raby, Christopher A. R.; Barrese, Vincenzo; Ramsey, John (Frontiers in Psychiatry, 2018)
3,4-dichloromethylphenidate (3,4-CTMP) and ethylphenidate are new psychoactive substances and analogs of the attention deficit medication methylphenidate. Both drugs have been reported on online user fora to induce effects similar to cocaine. In the UK, 3,4-CTMP appeared on the drug market in 2013 and ethylphenidate has been sold since 2010. We aimed to explore the neurochemical effects of these drugs on brain dopamine and noradrenaline efflux. 3,4-CTMP and ethylphenidate, purchased from online vendors, were analyzed using gas chromatography and mass spectroscopy to confirm their identity. Drugs were then tested in adolescent male rat brain slices of the nucleus accumbens and stria terminalis for effects on dopamine and noradrenaline efflux respectively. Fast cyclic voltammetry was used to measure transmitter release. Methylphenidate (10 μM) increased evoked dopamine and noradrenaline efflux by 4- and 2-fold, respectively. 3,4-CTMP (0.1 and 1 μM) increased evoked dopamine and noradrenaline efflux by 6-fold and 2-fold, respectively. Ethylphenidate (1 μM) doubled evoked dopamine and noradrenaline efflux in both cases. 3,4-CTMP's effect on dopamine efflux was greater than that of methylphenidate, but ethylphenidate appears to be a weaker dopamine transporter inhibitor. Experiments using the dopamine D2 antagonist haloperidol, the noradrenaline α2 receptor antagonist yohimbine, the dopamine transporter inhibitor GBR12909 and the noradrenaline transporter inhibitor desipramine confirmed that we were measuring dopamine in the accumbens and noradrenaline in the ventral BNST. All three psychostimulant drugs, through their effects on dopamine efflux, may have addictive liability although the effect of 3,4-CTMP on dopamine suggests that it might be most addictive and ethylphenidate least addictive.